O073 Triple neuroprotection during emergency carotid endarterectomy for acute stroke after failed TPA or beyond the 24-hour window of opportunity. (22nd July 2022) - Sultan, S; Acharya, Y; Hynes, N
Abstract: Introduction: Clinical dilemma during tissue plasminogen activator (tPA) failure in ischemic stroke management is a daunting challenge. We propose an innovative approach called triple neuro-protection (TNP), which encompasses three technical domains - targeted hypothermia, systemic induced hypertension, and barbiturates infusion. Methods: From 2002–2019, we performed 832 carotid interventions amongst more than 12, 000 patients referred to our tertiary vascular services with carotid artery disease. Amongst them, 25 patients presented between March 2015 and 2019 with acute dense stroke with either failed tPA or passed the recommended timing for acute stroke intervention. Fifteen (60%) had hemineglect with acute infarct on MRI brain and a Rankin score of 4 or 5, and 96% had 80–99% stenosis on the symptomatic side (mean ABCD3-I score 11.35). All patients underwent emergency carotid endarterectomy (CEA) with therapeutically induced hypothermia (32–34°C), targeted hypertension (systolic blood pressure 180–200 mm of Hg), and brain suppression with a barbiturate. Results: There were no perioperative complications and mortality. There were no myocardial infarction cases, death, cranial nerve injury, wound hematoma, or procedural bleeding. Mean hospital stay was 8.4±5.5 days. All patients had resolution of neurological symptoms, except three (failed thrombolysis previously). Eighty percent had a postoperative Rankin score of 0 on discharge, and 88% of patients were discharged home with three requiring rehabilitation. Conclusion: We observed positive neurological outcomes without serious adverse events with TNP during emergency CEA in acute brain injury patients. Based on our experience, we recommend a large scale study on TNP. Take-home message: Triple neuroprotection showed positive neurological outcomes without serious adverse events during emergency carotid endarterectomy in acute brain injury patients.